'I do not care a pin about it myself' - Honey, A (Chawton House Library, 2016)
Andrew Honey, Book Conservator at the Bodleian, tells us of his excitement at discovering an original Jane Austen pin on our Sir Charles Grandison manuscript, and what this, and other pins, tell us about their use.